The Japanese Communist movement, 1920-1966 - [by] Robert A. Scalapino. (University of California Press, 1967)
"Sources": p. [355]-366. Bibliographical footnotes. "Jointly sponsored by The Rand Corporation and The Center for Japanese and Korean Studies, University of California, Berkeley."